Uji stabilitas fisik formulasi sediaan sirup infusa daun seledri (Apium graveolens L.) dengan larutan pemanis daun stevia (Stevia rebaudiana) - Dewi, Indri Kusuma; Alif, Salsa Billa Nur; Ridlo, Achmad (Borobudur Pharmacy Review, 2024)
One of the cardiovascular diseases is commonly known as hypertension, which is high blood pressure. It is recognized as a cause of death and is often referred to as the "silent killer." This is because hypertension frequently occurs without symptoms and is only detected after it has caused serious damage to the body. Many hypertension sufferers utilize traditional therapies, one of which is the use of celery plants (Apium graveolens L.). Utilization of celery planted could have been made into a syrup that used natural sweetener content, namely natural sweetener stevia left (Stevia rebaudiana). This research aims to determine the effect of storage time on the results of the stability test of celery leaf syrup preparations with stevia leaf sweetener using the cycled tested method which carried out as many as 6 cycles with temperatures of 4oC and 40oC each for 24 hours by testing parameters included organoleptic, pH, viscosity, clarity and homogeneity. This type of research uses experimental research. The results of the stability of celery leaf infusion syrup preparation (Apium graviolens L.) obtained by the organoleptic test were liquid, had a distinctive celery smell and were yellowish green in color. Celery syrup preparation is homogeneous and cleared during storage, the pH test stability results had an average value of 5.27 and a viscosity of 3.8 cP. The results of the stability tests for organoleptic properties, homogeneity, clarity, pH, and viscosity indicate that no significant differences were found between the cycles, meaning the syrup remains stable during storage